Reduction of regulatory T cells in skin lesions but not in peripheral blood of patients with systemic scleroderma - Klein, S.; Kretz, C. C.; Ruland, V.; Stumpf, C.; Haust, M.; Hartschuh, Wolfgang; Hartmann, Martin; Enk, Alexander; Suri-Payer, Elisabeth; Oberle, Nina; Krammer, Peter H.; Kuhn, Annegret (Annals of the rheumatic diseases, 2011)
Objective To determine the frequency and suppressive capacity of regulatory T cells (Treg) and their association with clinical parameters in patients with systemic scleroderma (SSc). - Methods Peripheral blood from 25 patients with SSc, 15 patients with localised scleroderma (LS) and 29 healthy controls (HC) was studied. Analysis of CD4+ forkhead box P3 (Foxp3)+ and CD4+CD25++Foxp3+ Treg subpopulations was carried out by flow cytometry and cell proliferation was quantified by 3H-thymidine incorporation. Quantitative analysis of Treg was further performed in skin biopsies from 17 patients with SSc and 21 patients with LS using anti-CD4 and anti-Foxp3 monoclonal antibodies for immunohistochemistry. - Results The frequency of CD4+Foxp3+ and CD4+CD25++Foxp3+ Treg in peripheral blood from patients with SSc was not significantly different from that of patients with LS or HC. The suppressive capacity of CD4+CD25++ Treg in SSc was also found to be similar to that of HC. Phenotypic and functional data revealed no significant difference between the limited or diffuse form of SSc. Moreover, therapy with bosentan showed no significant effect on the frequency of Treg during the course of the disease. However, the frequency of Treg in skin lesions from patients with SSc or LS, determined as the percentage of CD4+ cells expressing Foxp3 in the inflammatory infiltrate, was significantly reduced compared with other inflammatory skin diseases. - Conclusion These results indicate that although the authors found no defect in the frequency or function of peripheral Treg subpopulations, the reduction of CD4+Foxp3+ Treg in the skin of patients with SSc may be important in the pathogenesis of the disease.